Levers and mixtures: An integrated science and mathematics activity to solve problems. (3rd April 2017) - Alpaslan, Muhammet Mustafa
ABSTRACT: In recent years, the integration of science and mathematics has become popular among educators because of its potential benefits for student learning. The purpose of this study is to introduce a two-day interdisciplinary lesson that brings science and mathematics concepts together, actively engaging students in working with percentages of the ingredients in mixtures with the concept of torque. Participation in this Grade 7-9 lesson provides opportunities for students to learn from both content areas as they progress through a variety of science process skills.